Effectiveness of an Instructional Program for Teachers about Students' School Phobia at Primary Schools - Shaimaa Ab. Kkadim, Suad Hassoon Khudhair (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Evaluate the effectiveness of the instructional program for teacher's knowledge's about student's school phobia at primary school. Study design: A quasi-experimental design was implemented in the research to achieve the study goals by using pre- and post-tests for one group of teachers in primary school. in Al- Amara Region. The study has been carried out during the period extended from the 23th december 2021 to 20th July 2022. Data collection: The permission was presented to the Ministry of education- office of Misan provenance/ deparment of oversight specialist to ensure the research agreement and cooperation and to provide access the these school facilities. In order to attain precise data and illustrative sample , non-probability (purposive) sample is carefully chosen which consists of (25) teachers Conclusion: Illustrated from this study, the teachers have poor knowledge regarding primary students school phobia at pretest in study group. Association between teachers' knowledge and their (gender, level of education, years of experience and main source of information.